Storytelling as a teaching method in drawing for children between the ages of 3 to 6 / Chia Chua Hang - Chia, Chua Hang (2017)
This research examines storytelling as a method in developing drawing for children between the ages of 3 to 6. It also investigates the relationship between storytelling and the drawing process. This research argues that existing methods in drawing forces children to copy from images and does not help them to express themselves. In this traditional technique of teaching drawing through copying, children are expected to reproduce whatever they see accurately. This technique does not encourage exploration, focus and confidence in drawing. In contrast, storytelling as a teaching method can spur creative exploration, encourage focus and cultivate confidence. This research will use qualitative methods of observation to assess the effectiveness of storytelling as a teaching method within the classroom. The findings show that storytelling can be employed to supplement existing traditional techniques of teaching.